Programmed Cell Death Protein 1 Blockade Reduces Glycogen Synthase Kinase 3β Activity and Tau Hyperphosphorylation in Alzheimer’s Disease Mouse Models - Zou, Yulian; Gan, Chen-Ling; Xin, Zhiming; Zhang, Hai-Tao; Zhang, Qi; Lee, Tae Ho; Pan, Xiaodong; Chen, Zhou (Frontiers in Cell and Developmental Biology, 2021)
Alzheimer's disease (AD) is a central nervous system degenerative disease, with no effective treatment to date. Administration of immune checkpoint inhibitors significantly reduces neuronal damage and tau hyperphosphorylation in AD, but the specific mechanism is unclear. Here, we found that programmed cell death-receptor 1 (PD1) and its ligand PDL1 were induced by an intracerebroventricular injection of amyloid-β; they were significantly upregulated in the brains of APP/PS1, 5×FAD mice and in SH-SY5Y-APP cell line compared with control. The PD1 and PDL1 levels positively correlated with the glycogen synthase kinase 3 beta (GSK3β) activity in various AD mouse models, and the PDL1-GSK3β immune complex was found in the brain. The application of PD1-blocking antibody reduced tau hyperphosphorylation and GSK3β activity and prevented memory impairments. Mechanistically, we identified PD1 as a critical regulator of GSK3β activity. These results suggest that the immune regulation of the PD1/PDL1 axis is closely involved in AD.